Strategies for maximizing the effectiveness of virtual teams in the construction industry - Mohamed, Omar Abdelnaby (2019)
Construction projects have been expanding exponentially during the past few years, yet the labor productivity is still low compared to other sectors’ productivity. Expansions in construction labor productivity contribute to the economy. Therefore, an immense effort should be applied in managing construction projects. Scientific breakthroughs have resulted in a group of individuals working together from different geographic locations that rely on communication technologies to collaborate (i.e., virtual team). Along with other factors, virtual teams are affecting construction labor productivity. Therefore, it is clear that virtual team also requires attention to boost construction productivity. This study aims to identify the most common strategies used to maximize the effectiveness of virtual teams in the construction industry. Individual interviews were conducted throughout this research. The findings of this study are expected to increase the level of understanding of virtual teams in the construction industry.